The determinants of motivation and adherence regarding top competitive basketball of juniors - Simkova, K. (2019)
The thesis deals with the topic of motivation and adherence of junior (cadet) players of basketball in Slovak Republic. In the practical part of the thesis, it presents the results of a qualitative study focused on the determinants of motivation to continue playing professionally among basketball players (boys and girls) between the age 15-18. Two groups (20 girls and 20 boys) in the Slovakia have undergone a semi-structured interviews based on the Career transition theory. A qualitative analysis revealed eight determinants of motivation and adherence - lifestyle; perception of own competences; basketball specifics; time management; health - biopsychosocial aspect; enthusiasm; environment; atmosphere - team spirit. Before the stage of self-realisation, the junior players are already aware if they intend to continue to the mastery stage or not (in regards to the career transition theory). The time management is the only determinant that strongly influenced the dropout rate from the basketball career. In cases of both boys and girls, the results were the same with regards the future profession and practising of recreational sports. They wish to continue being the part of the sports environment, even if not professionally. The outcome of the study is an extensive insight into how the young generation perceives sports as such. Awareness of all the topics can serve as a basis to further explore the qualitative aspects of motivation and adherence to a certain sport and its popularity based on the culture and country, they grow up in.